The Concept of Circular Economy in the Implementation of Source-Based Waste Management in Bali - Muliarta, I Nengah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bali, which is a world tourist destination, is still facing a waste problem because the amount of waste is increasing along with the increase in the number of tourists. The Suwung landfill, as the largest waste disposal site in Bali, is no longer able to accommodate the increasing amount of waste production. Tackling waste problems The Provincial Government of Bali issued Bali Governor Regulation Number 47 of 2019 concerning Source-Based Waste Management. Source-based waste management provides an opportunity for the community to be creative in processing the waste they produce, such as compost, liquid organic fertilizer, eco-enzymes, brackets, or biopesticides. Source-based waste management efforts require support from various parties, including banks. Banks can also play an important role in education and social campaigns about the importance of managing waste.